Pemanfaatan Briket Arang Kulit Pinang sebagai Bahan Bakar Alternatif di Desa Rumah Galuh, Kec Sei Bingai, Kab Langkat - Eka Bobby Febrianto; Ingrid Ovie Yosephine; Marzuti Isra; Ismi Aryati; Ade Kurniawan Nasution (Yayasan Literasi Sains Indonesia, 2024)
Fuel oil, coal and gas are some of the energy sources that are widely used by the people of Indonesia. Charcoal briket are a biomass energy source that is biodegradable and environmentally friendly which is one of the alternative fuels. The basic material for making briket charcoal consists of various materials such as agricultural, plantation, and household waste. One of the agricultural commodities of the community of Rumah Galuh Village, Sei Bungai District, Langkat Regency is areca nut. Solid waste in the form of areca nut peel has the potential to be used in briket making materials that can increase the use and economic value of the waste. The implementation procedure starts from burning, grinding, sieving, making adhesives, making dough, molding, drying briket, to testing briket, then socialization to the community. As the ultimate goal of Community Service, with this activity, areca nut skin waste which is usually only burned can be used as goods of economic value, providing education to the community regarding the use of areca nut skin waste into charcoal briket so that in the future it can increase the income of the people of Rumah Galuh Village.